A calculus problem by Kushal Bose

Calculus Level 5

e ( x 2 + x y + y 2 ) d y d x \large \displaystyle \int_{-\infty}^{\infty} \int_{-\infty}^{\infty} e^{-(x^2+xy+y^2)} \, dy\, dx

Evaluate the above integral. The answer will come in the form of a π c b \dfrac{a \pi}{\sqrt[b]{c}} where a , b , c a,b,c are positive integers and c c can not be reduced again.

Submit the answer as a + b + c a+b+c


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

I = R 2 e ( x 2 + x y + y 2 ) d x d y = R 2 e ( x + y 2 ) 2 3 y 2 4 d x d y = 2 3 R 2 e ( u 2 + v 2 ) d u d v By the transformation x + y 2 = u 3 2 y = v = 2 3 ( R e x 2 d x ) 2 = 2 π 3 \displaystyle \begin{aligned} I &=\int_{\mathbb{R}^2} e^{-(x^2+xy+y^2)}\;dx\; dy \\ &= \int_{\mathbb{R}^2} e^{-\left(\large{x}+\dfrac{y}{2}\right)^2-\dfrac{3y^2}{4}}\; dx \; dy \\ &= \dfrac{2}{\sqrt{3}} \int_{\mathbb{R}^2} e^{-(u^2+v^2)}\;du\;dv \quad\text{By the transformation } x+\dfrac{y}{2}=u\quad \dfrac{\sqrt{3}}{2}y=v \\ &= \dfrac{2}{\sqrt{3}}\left(\int_{\mathbb{R}}e^{-x^2}\; dx\right)^2 \\ &= \dfrac{2\pi}{\sqrt{3}}\end{aligned}

Note: The jacobian of the transformation x + y 2 = u , 3 y = 2 v x+\dfrac{y}{2}=u,\sqrt{3}y=2v is as follows :

J = 1 1 3 0 2 3 = 2 3 \displaystyle J = \begin{vmatrix} 1 & -\dfrac{1}{\sqrt{3}} \\ 0 & \dfrac{2}{\sqrt{3}} \end{vmatrix} = \dfrac{2}{\sqrt{3}}

Great ....

Kushal Bose - 4 years, 1 month ago
Guilherme Niedu
May 4, 2017

Use polar coordinates, x = r cos θ , y = r sin θ , J = r x = r \cos \theta, y = r \sin \theta, |J| = r :

= π π 0 r e ( r 2 + r 2 cos θ sin θ ) d r d θ \large \displaystyle = \int_{-\pi}^{\pi} \int_0^{\infty} r e^{-(r^2 + r^2 \cos \theta \sin \theta) } dr d \theta

= π π [ e r 2 ( 1 + cos θ sin θ ) 2 ( 1 + cos θ sin θ ) ] 0 d θ \large \displaystyle = \int_{-\pi}^{\pi} \left [ \frac{ e^{-r^2 ( 1 + \cos \theta \sin \theta) }}{2 (1 + \cos \theta \sin \theta ) } \right ]_{\infty}^0 d \theta

= 1 2 π π 1 1 + cos θ sin θ d θ \large \displaystyle = \frac12 \int_{-\pi}^{\pi} \frac{1}{1 + \cos \theta \sin \theta} d \theta

= 1 2 2 π 2 π 2 1 1 + cos θ sin θ sec 2 θ sec 2 θ d θ \large \displaystyle = \frac12 \cdot 2 \cdot \int_{- \frac{\pi}{2}}^{\frac{\pi}{2}} \frac{1}{1 + \cos \theta \sin \theta} \color{#3D99F6} \cdot \frac{\sec^2 \theta} {\sec^2 \theta} \color{#333333} d \theta

= π 2 π 2 sec 2 θ sec 2 θ + tan θ d θ \large \displaystyle = \int_{- \frac{\pi}{2}}^{\frac{\pi}{2}} \frac{\sec^2 \theta}{\sec^2 \theta + \tan \theta} d \theta

u = tan θ d u = sec 2 θ d θ \color{#20A900} \large \displaystyle u = \tan \theta \implies du = \sec^2 \theta d \theta

= 1 u 2 + u + 1 d u \large \displaystyle = \int_{-\infty}^{\infty} \frac{1}{u^2 + u + 1} du

= 1 ( u + 1 2 ) 2 + 3 4 d u \large \displaystyle = \int_{-\infty}^{\infty} \frac{1}{(u + \frac12)^2 + \frac34} du

v = u + 1 2 d v = d u \color{#20A900} \large \displaystyle v = u + \frac12 \implies dv = du

= 1 v 2 + 3 4 d v \large \displaystyle = \int_{-\infty}^{\infty} \frac{1}{v^2 + \frac34} dv

= 4 3 1 ( 2 3 v ) 2 + 1 d v \large \displaystyle = \frac43 \int_{-\infty}^{\infty} \frac{1}{ (\frac{2}{\sqrt{3}}v)^2 + 1} dv

= 4 3 3 2 tan 1 ( 2 3 v ) \large \displaystyle = \frac43 \cdot \frac{\sqrt{3}}{2} \cdot \tan^{-1} (\frac{2}{\sqrt{3}}v) \Bigg | _{-\infty}^{\infty}

= 2 3 3 [ π 2 ( π 2 ) ] \large \displaystyle = \frac{2 \sqrt{3}}{3} \cdot \left [ \frac{\pi}{2} - \left ( -\frac{\pi}{2} \right ) \right]

= 2 π 3 3 \large \displaystyle = \frac{2 \pi \sqrt{3}}{3}

= 2 π 3 \color{#20A900} \large \displaystyle = \boxed {\large \displaystyle \frac{2 \pi}{\sqrt{3}} }

Then:

a = 2 , b = 2 , c = 3 , a + b + c = 7 \color{#3D99F6} \large \displaystyle a = 2, b = 2, c = 3, \boxed {\large \displaystyle a + b + c = 7 }

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...